Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of the Someshwar Mahadev temple from the western side. To its north is Gamela talava(lake). Faintly in the background can be seen the Kumbheswar Mahadev temple. The entire wall projections, built in schist stone, are adorned with imagery of gods, goddesses, apsaras and ascetics. These consist of the Shaiva images inside principal niches – Natesha, Andhakasuravadh, Chamunda and dikpalas that is the cardinal deities–Indra, Agni, Nritti, Vayu, Kuber and Ishana.